Pengendalian Kualitas Pengelasan Pada Project Fabrikasi Metal Duct MBI Menggunakan Metode SQC Dan FMEA - Tiara Nuriyah Sani; Sumiati Sumiati (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
The National Private Company PT Swadaya Graha, which is part of Semen Indonesia, is currently active in carrying out Metal Ducting (MD) fabrication projects in collaboration with PT Maxiterm Boiler Indonesia. During the production process, several types of welding defects are detected, such as Slag, Porosity, Spatter, and Incomplete Fusion. The aim of this research is to determine the most dominant percentage of welding defects, identify the causes of welding defect factors, and provide suggestions for suggestions for improving welding quality. This research uses the Statistical Quality Control (SQC) method and Failure Mode Effect Analysis (FMEA), using SQC tools such as check sheets, stratification, histograms, Pareto diagrams, scatter diagrams, P control charts, and cause and effect diagrams. Next, an FMEA analysis is carried out based on a cause and effect diagram to formulate proposed corrective actions. The results showed that the most dominant type of defect, based on cumulative percentage, was spatter (29.42%), followed by porosity (28.41%), Incomplete Fusion (21.59%), and slag (20.58%). Based on the RPN (Risk Priority Number) value, the Incomplete Fusion defect with the highest RPN value of 240 is caused by improper electrode angle determination. Repair recommendations involve checking the electrode angle according to the WPS used before starting the welding process.